EXPLORATION OF LOCAL WISDOM IN HANDLING COVID 19 IN NAGARI SITUJUAH BATUA - SURHERNI, SURHERNI (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
AbstractThe rise of news on the handling of Covid-19 in the Situjuah Batua Nagari Government, Situjuah Limo Nagari District, Limapuluh Kota Regency, West Sumatra in various electronic media has sparked the author's curiosity to take a deeper look at its culture and history. Nagari's efforts in dealing with COVID-19 are considered more responsive so that it is deemed successful in adapting to the current pandemic conditions. The Nagari's ability to optimize existing local resources and wisdom is thought to be the source of this success. This research aims to explore local wisdom that supports the social institutions of the Situjuah Batua community in dealing with COVID-19. Furthermore, this research seeks to identify local wisdom that affects the community and develop strategies to raise awareness about efforts to deal with and prevent COVID-19. This research uses a qualitative method with an observation and interview approach related to handling COVID-19. Local wisdom (togetherness; cooperation; deliberation; commitment to customs and tools) in Nagari Situjuah Batu mobilizes all components or elements in Nagari to make behavioral changes due to the COVID-19 pandemic. Therefore, behavior change is one of the determining factors for successfully handling the Covid-19 pandemic in Nagari Situjuah Batua